2012
DOI: 10.4049/jimmunol.1102175
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Pathways of Death ofHistoplasma capsulatum-Infected Macrophages: Implications for the Immunopathogenesis of Early Infection

Abstract: Apoptosis of leukocytes is known to strongly influence the immunopathogenesis of infection. Herein, we dissected the death pathways of murine Mφ infected with the intracellular pathogen, Histoplasma capsulatum. Yeast cells caused apoptosis of Mφ at a wide range of multiplicity of infection, but smaller inocula resulted in delayed detection of apoptosis. Upon infection, caspases 3 and 1 were activated, and both contributed to cell death but only the former was involved in apoptosis. The principal driving force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 59 publications
1
43
0
Order By: Relevance
“…These combined data sets open the possibility that Cn -induced phagolysosome damage may enhance programmed cell death in macrophages. Intriguingly, lysosome damage induced by ground silica has been shown to induce inflammasome activation and pyroptosis in activated macrophages (35, 52) consistent with the observed activation of caspase-1 in cells infected with fungal pathogens (5356). Lysosome damage can also have a role in apoptosis as released lysosomal cathepsins can cleave apoptosis proteins to initiate programed cell death in cultured fibroblasts (5765).…”
Section: Discussionsupporting
confidence: 64%
“…These combined data sets open the possibility that Cn -induced phagolysosome damage may enhance programmed cell death in macrophages. Intriguingly, lysosome damage induced by ground silica has been shown to induce inflammasome activation and pyroptosis in activated macrophages (35, 52) consistent with the observed activation of caspase-1 in cells infected with fungal pathogens (5356). Lysosome damage can also have a role in apoptosis as released lysosomal cathepsins can cleave apoptosis proteins to initiate programed cell death in cultured fibroblasts (5765).…”
Section: Discussionsupporting
confidence: 64%
“…Fer‐1 prevents non‐apoptotic death of macrophages infected with H. capsulatum: Previous studies examining macrophage death driven by H. capsulatum described apoptosis as the predominate death mechanism . Here, we found that death of infected bone‐marrow‐derived macrophages (BMDMs) in vitro was non‐apoptotic.…”
Section: Resultsmentioning
confidence: 73%
“…Death of infected macrophages is an important part of the interaction between pathogen and host. Previous studies have focused on the classic caspase‐dependent cell death process: apoptosis . Although the exact biochemical sequence in infected macrophage apoptosis is unknown, it is dependent on the fungal gene cbp1 and involves endoplasmic reticulum stress and release of the pro‐inflammatory cytokine tumor necrosis factor‐α (TNF‐α).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum of this illness ranges from an asymptomatic, self-limited illness to a progressive disseminated disease. The primary focus of this fungal infection is the lung, and the disease prognosis depends on the host immune response, the fungal inoculum size inhaled, and the fungal virulence (Deepe and Buesing, 2012). Immunocompromised subjects, especially individuals with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS), patients undergoing corticosteroid or other forms of immunosuppressive therapy, and those undergoing cytotoxic chemotherapy, can develop more severe forms of the disease, due to fungal dissemination to several organs (Damasceno et al, 2013;Kauffman, 2007).…”
Section: Introductionmentioning
confidence: 99%